2023
DOI: 10.3390/life13030716
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying the Value of Minimal Clinically Important Difference in the Cardiothoracic Surgery Context

Abstract: The aim of this review is to describe the different statistical methods used in estimating the minimal clinically important difference (MCID) for the assessment of quality of life (QOL)-related and clinical improvement interventions, along with their implementation in cardiothoracic surgery. A thorough literature search was performed in three databases (PubMed/Medline, Scopus, Google Scholar) for relevant articles from 1980 to 2022. We included articles that implemented and assessed statistical methods used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…M(C)ID now routinely informs sample size calculations for clinical trials and is often used to interpret scores from patient-reported outcome (PRO) instruments. Despite its importance, M(C)ID remains poorly utilized, particularly in the surgical literature, 10–12 likely due to the dearth of PRO studies in the field. In accordance, the 2023 Zurich-Danish conference included defining and utilizing clinically meaningful measures as a consensus recommendation for improving the quality of surgical outcomes research 13 …”
mentioning
confidence: 99%
“…M(C)ID now routinely informs sample size calculations for clinical trials and is often used to interpret scores from patient-reported outcome (PRO) instruments. Despite its importance, M(C)ID remains poorly utilized, particularly in the surgical literature, 10–12 likely due to the dearth of PRO studies in the field. In accordance, the 2023 Zurich-Danish conference included defining and utilizing clinically meaningful measures as a consensus recommendation for improving the quality of surgical outcomes research 13 …”
mentioning
confidence: 99%